The labeling of unsaturated γ‐hydroxybutyric acid by heavy isotopes of hydrogen: iridium complex‐mediated H/D exchange by C─H bond activation vs reduction by boro‐deuterides/tritides. (4th September 2016) - Marek, Aleš; Pedersen, Martin H.F.; Vogensen, Stine B.; Clausen, Rasmus P.; Frølund, Bente; Elbert, Tomáš
Abstract : 3‐Hydroxycyclopent‐1‐ene‐1‐carboxylic acid (HOCPCA (1 )) is a potent ligand for high‐affinity γ‐hydroxybutyric acid binding sites in the central nervous system. Various approaches to the introduction of a hydrogen label onto the HOCPCA skeleton are reported. The outcomes of the feasible C─H activation of olefin carbon (C‐2) by iridium catalyst are compared with the reduction of the carbonyl group (C‐3) by freshly prepared borodeuterides. The most efficient iridium catalysts proved to be Kerr bulky phosphine N ‐heterocyclic species providing outstanding deuterium enrichment (up to 91%) in a short period of time. The highest deuterium enrichment (>99%) was achieved through the reduction of ketone precursor2 by lithium trimethoxyborodeuteride. Hence, analogical conditions were used for the tritiation experiment. [ 3 H]‐HOCPCA selectively labeled on the position C‐3 was synthetized with radiochemical purity >99%, an isolated yield of 637 mCi and specific activity = 28.9 Ci/mmol. Abstract : Various approaches to the introduction of a hydrogen label onto the HOCPCA skeleton are reported. The outcomes of the feasible C─H activation of olefin carbon (C‐2) by iridium catalyst are compared with the reduction of the carbonyl group (C‐3) by freshly prepared borodeuterides.